2021
DOI: 10.3390/metabo11080551
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Risk Factors in Children with Obesity, Preventive Diagnostics and Possible Interventions

Abstract: The increasing burden of obesity plays an essential role in increased cardiovascular morbidity and mortality. The effects of obesity on the cardiovascular system have also been demonstrated in childhood, where prevention is even more important. Obesity is associated with hormonal changes and vascular dysfunction, which eventually lead to hypertension, hyperinsulinemia, chronic kidney disease, dyslipidemia and cardiac dysfunction—all associated with increased cardiovascular risk, leading to potential cardiovasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 135 publications
(150 reference statements)
0
14
0
Order By: Relevance
“…Obesity, a crucial risk factor for chronic diseases, is progressively becoming a global health issue [1,2], with its prevalence increasing dramatically worldwide [3]. Obesity is associated not only with cardiovascular diseases in children [4] but also with vascular dysfunction and hormonal changes, leading to hypertension, dyslipidaemia and potential cardiovascular events in transitional-aged youth [5]. The transitional age period during youth is an important stage from adolescence to adulthood, ranging from the ages of 16 to 24 years [6].…”
Section: Introductionmentioning
confidence: 99%
“…Obesity, a crucial risk factor for chronic diseases, is progressively becoming a global health issue [1,2], with its prevalence increasing dramatically worldwide [3]. Obesity is associated not only with cardiovascular diseases in children [4] but also with vascular dysfunction and hormonal changes, leading to hypertension, dyslipidaemia and potential cardiovascular events in transitional-aged youth [5]. The transitional age period during youth is an important stage from adolescence to adulthood, ranging from the ages of 16 to 24 years [6].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, an investigation that took place in the Bogalusa Heart Study outlined that total cholesterol, LDL cholesterol, and triglycerides were 2.4 to 7.1 times more likely to be elevated in overweight children. (23) . Also, another study revealed that abnormal changes compatible with an atherogenic lipid profile were present in obese subjects (24) .…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5] Specifically, the metabolic profile is hugely affected by obesity, including hyperinsulinemia, dyslipidemia, impaired fasting glucose, or hypercholesterolemia. [6][7][8] The severity of obesity increases with continuous weight gain and tends to have higher all-cause mortality and mortality due to a wide range of other serious health complications. The negative impact of obesity also increases in the presence of other diseases, for example, diabetes.…”
Section: Obesity and Its Complicationmentioning
confidence: 99%